Chromosomal Mapping of Repetitive DNAs in Characidium (Teleostei, Characiformes): Genomic Organization and Diversification of ZW Sex Chromosomes - Scacchetti, Priscilla C. [UNESP]; Utsunomia, Ricardo [UNESP]; Pansonato-Alves, Jose C. [UNESP]; Vicari, Marcelo R.; Artoni, Roberto F.; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Karger, 2015)
The speciose neotropical genus Characidium has proven to be a good model for cytogenetic exploration. Representatives of this genus often have a conserved diploid chromosome number; some species exhibit a highly differentiated ZZ/ZW sex chromosome system, while others do not show any sex-related chromosome heteromorphism. In this study, chromosome painting using a W-specific probe and comparative chromosome mapping of repetitive sequences, including ribosomal clusters and 4 microsatellite motifs - (CA)(15), (GA)(15), (CG)(15), and (TTA)(10) -, were performed in 6 Characidium species, 5 of which possessed a heteromorphic ZW sex chromosome system. The W-specific probe showed hybridization signals on the W chromosome of all analyzed species, indicating homology among the W chromosomes. Remarkably, a single major rDNA-bearing chromosome pair was found in all species. The 18S rDNA localized to the sex chromosomes in C. lanei, C. timbuiense and C. pterostictum, while the major rDNA localized to one autosome pair in C. vidali and C. gomesi. In contrast, the number of 5S rDNA-bearing chromosomes varied. Notably, minor ribosomal clusters were identified in the W chromosome of C. vidali. Microsatellites were widely distributed across almost all chromosomes of the karyotypes, with a greater accumulation in the subtelomeric regions. However, clear differences in the abundance of each motif were detected in each species. In addition, the Z and W chromosomes showed the differential accumulation of distinct motifs. Our results revealed variability in the distribution of repetitive DNA sequences and their possible association with sex chromosome diversification in Characidium species. (C) 2015 S. Karger AG, Basel
Keywords: Chromosome painting; Crenuchidae; Fish cytogenetics; Karyotype diversification